2005
DOI: 10.3233/jad-2005-7304
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective phagocytosis of amyloid-β by macrophages of Alzheimer's disease patients

Abstract: The defective clearance of amyloid-β (Aβ) in the brain of Alzheimer's disease (AD) patients is unexplained. The immunohistochemical studies of the frontal lobe and hippocampus show perivascular and intraplaque infiltration by blood-borne macrophages containing intracellular Aβ but only inefficient clearance of Aβ deposits. Neurons and neuronal nuclei, respectively, express interleukin-1β and the chemokine RANTES, which could induce the inflammatory cell infiltration. To clarify the pathophysiology of Aβ cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
216
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(227 citation statements)
references
References 52 publications
9
216
0
2
Order By: Relevance
“…This finding implies a potential role for mPGES-1 in microglial phagocytosis of Aβ plaques, a result consistent with that of a previous study [29]. In addition, our results indicate that mPGES-1 is constitutively expressed in human microglia.…”
Section: Discussionsupporting
confidence: 93%
“…This finding implies a potential role for mPGES-1 in microglial phagocytosis of Aβ plaques, a result consistent with that of a previous study [29]. In addition, our results indicate that mPGES-1 is constitutively expressed in human microglia.…”
Section: Discussionsupporting
confidence: 93%
“…Lue et al (2001) have reported that 13-15 d in vitro cultures of microglia derived from human AD patients secrete elevated levels of IL-1␤, TNF␣, IL-6, and MCP-1 (monocyte chemoattractant protein 1) compared with control microglia. Others have demonstrated that peripheral blood-derived macrophages from AD patients have reduced capacity to phagocytose A␤ compared with cells from agematched controls (Fiala et al, 2005). Together, these data illustrate that adult AD microglia appear to respond fundamentally different to A␤ stimulation compared with control cells and complement our observations of differences between aged and .…”
Section: Discussionsupporting
confidence: 78%
“…For this reason AD has been always considered as a brain disease (Selkoe, 2001). Recently it was suggested that the inflammation induced by the accumulation of Aβ is not an only a local phenomenon but can induce systemic symptoms or be caused by systemic events (Britschgi and Wyss-Coray, 2007;Richartz-Salzburger et al, 2007;Fiala et al, 2005). Moreover, it is likely that Aβ is not only accumulated in the brains of AD patients, but is also present in the periphery and can be detected in the blood (Britschgi and Wyss-Coray, 2007;Mayeux et al, 2003;Sagare et al, 2011).…”
Section: Discussionmentioning
confidence: 99%